Exploring strategies to reach individuals of Turkish and Moroccan origin for health checks and lifestyle advice: a mixed-methods study. Issue 1 (December 2016) - Bukman, Andrea; Teuscher, Dorit; Ben Meftah, Jamila; Groenenberg, Iris; Crone, Mathilde; van Dijk, Sandra; Bos, Marieke; Feskens, Edith
Abstract Background Low participation rates among ethnic minorities in preventive healthcare services are worrisome and not well understood. The objective of this study was to explore how adults of Turkish and Moroccan origin living in the Netherlands, aged 45 years and older, can be reached to participate in health checks for cardio-metabolic diseases and follow-up (lifestyle) advice. Methods This mixed-methods study used a convergent parallel design, to combine data of one quantitative study and three qualitative studies. Questionnaire data were included of 310 respondents, and interview data from 22 focus groups and four individual interviews. Participants were recruited via a research database, general practitioners and key figures. Quantitative data were analysed descriptively and qualitative data were analysed using a thematic approach. Results Regarding health checks, 50 % (95 % CI 41;59) of the Turkish questionnaire respondents and 66 % (95 % CI 57;76) of the Moroccan questionnaire respondents preferred an invitation from their general practitioner. The preferred location to fill out the health check questionnaire was for both ethnic groups the general practitioner's office or at home, on paper. Regarding advice, both groups preferred to receive advice at individual level rather than in a group, via either a physician or a specialised healthcare professional. It was emphasised that the person who gives lifestyle advice should be familiar with the (eating) habits of the targeted individual. Sixty-one percent (95 % CI 53;69) of the Turkish respondents preferred to receive information in their native language compared to 37 % (95 % CI 29;45) of the Moroccan respondents. Several participants mentioned a low proficiency in the local language as an explanation for their preference to fill out the health check questionnaire at home, to receive advice from an ethnic-matched professional, and to receive information in their native language. Conclusions The general practitioner is considered as a promising contact to reach adults of Turkish and Moroccan origin for health checks or (lifestyle) advice. It might be necessary to provide information in individuals' native language to overcome language barriers. In addition, (lifestyle) advice must be tailored. The obtained insight into preferences of Turkish and Moroccan adults regarding reach for preventive healthcare services could help professionals to successfully target these groups.